Solidarity and fair taxation in TU games - André Casajus (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2012)
We consider an analytic formulation/parametrization of the class of efficient, linear, and symmetric values for TU games that, in contrast to previous approaches, which rely on the standard basis, rests on the linear representation of TU games by unanimity games. Unlike most of the other formulae for this class, our formula allows for an economic interpretation in terms of taxing the Shapley payoffs of unanimity games. We identify those parameters for which the values behave economically sound, i.e., for which the values satisfy desirability and positivity. Put differently, we indicate requirements on fair taxation in TU games by which solidarity among players is expressed.
Keywords: C71; D60; 330; shapley value; solidarity; taxation; desirability; positivity